Prioritisation of internal and external barriers for supply chain implementation in manufacturing companies: a Malaysian perspective - Islam, Rafikul; Anis, Azilah (Intechopen, 2018)
Manufacturing companies as well as service providers often encounter barriers in successful implementation of supply-chain management (SCM) principles and practices. The present research, through extensive literature review, has identified the main barriers of SCM implementation for Malaysian manufacturing companies. Having identified the list of barriers, the items in the list are prioritized by applying the Analytic Hierarchy Process (AHP). Ten respondents who have wide range of experiences in dealing with SCM, have provided the necessary inputs in the prioritization exercise. The individual AHP pairwise comparison matrices are aggregated and Superdecision software has been used to compute the priorities. From the generated ranks, the most critical barriers can easily be identified. The onus on the Malaysian manufacturing companies is to take note of the present research findings and take appropriate measures so that the full benefits of SCM can be reaped. Though the findings are valid in the Malaysian context, but judgments from people from other countries can be taken and a comparison of the results can be made.